Lies, Lies, and Lies. On Truth, Dishonesty, Deception, and Self-Deception - Löhrer , Guido (ETHICS IN PROGRESS, 2022)
My considerations are typological in nature. A lie is a disingenuous assertion made to another person with the intent of deceiving the other person into believing both that the assertion is true and that the liar believes it to be true. This definition is morally neutral. It requires a further, moral judgment to determine whether a lie is a good or a bad thing, or whether, in specified circumstances, a lie is morally right or wrong. However, what if the truth is not only occasionally contaminated but lies are spread en masse in order to make the addressees question their ability to judge or to induce collective self-deception? Beginning with small-scale use of lies, related variants of dishonesty – especially large scale, propagandistic uses of lies – are conceptually characterized and evaluated. Lies can be systematically distinguished via their purposes.